2016
DOI: 10.3892/ol.2016.5051
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro-edenite induces fibulin-3 overexpression in non-malignant human mesothelial cells

Abstract: Exposure to asbestos is associated with the development of mesothelioma. In addition to asbestos, other fibers have been identified as risk factors for malignant and non-malignant diseases of the lungs. Among these, fluoro-edenite (FE) was found in patients from Biancavilla (Sicily, Italy) with pleural and lung disease, suggesting its role for tumor expansion. In this context, the identification of early biomarkers useful for the diagnosis of cancer is mandatory. Fibulin-3 represents an important marker for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Therefore, it was hypothesized that the detection of high plasma levels of fibulin-3, observed in street cleaners from the Biancavilla area, may be due to FE exposure. However, volcanic particulate exposure did not affect fibulin-3 expression (126,127). …”
Section: Fibersmentioning
confidence: 89%
See 4 more Smart Citations
“…Therefore, it was hypothesized that the detection of high plasma levels of fibulin-3, observed in street cleaners from the Biancavilla area, may be due to FE exposure. However, volcanic particulate exposure did not affect fibulin-3 expression (126,127). …”
Section: Fibersmentioning
confidence: 89%
“…Intriguingly, it was demonstrated that plasma levels of fibulin-3 were significantly lower in the group of workers exposed to asbestos fibers compared to those exposed to FE (126), suggesting that asbestos disposal workers properly used the personal protective equipment according to the current regulations. By contrast, other workers, such as street cleaners exhibited high levels of fibulin-3, indicating that these workers should be better equipped in order to prevent injury caused by FE found in dust deposited on the ground (126).…”
Section: Fibersmentioning
confidence: 99%
See 3 more Smart Citations